Early Jurassic North Atlantic sea-surface temperatures from TEX86 palaeothermometry - Robinson, S; Ruhl, M; Astley, D; Naafs, B; Farnsworth, A; Bown, P; Jenkyns, H; Lunt, D; O'Brien, C; Pancost, R; Markwick, P (Wiley, 2016)
Early Jurassic marine palaeotemperatures have been typically quantified by oxygen-isotope palaeothermometry of benthic and nektonic carbonate and phosphatic macrofossils. However, records of Early Jurassic sea-surface temperatures (SSTs) that can be directly compared with General Circulation Model (GCM) simulations of past climates are currently unavailable. The TEX86 SST proxy is based upon the relative abundance of glycerol dialkyl glycerol tetraethers (GDGTs) preserved in organic-carbon-bearing sediments. This proxy has been used extensively on Cretaceous and Cenozoic materials and, in one study, Middle and Upper Jurassic sediments. Here TEX86 is applied, for the first time, to Lower Jurassic (Sinemurian–Pliensbachian) sediments cored at Deep Sea Drilling Project Site 547 in the North Atlantic. The abundance of GDGTs in these sediments is very low, despite biomarker and Rock-Eval data suggesting that thermal maturity is, generally, low. Sea-floor oxygenation and a high input of reworked terrestrially sourced organic matter may explain the low concentrations. For samples from which it was possible to quantify the relative abundance of GDGTs, TEX86 values range from 0.78 to 0.88, equating to SSTs in excess of >28˚C. These temperatures are broadly comparable with new GCM simulations of the Sinemurian and Pliensbachian stages and support the general view of a predominantly warm climate. The new proxy data suggest that, under favourable geological conditions, it is possible to extend the record of TEX86-based SSTs back into the Early Jurassic.